Engineers in India Number and Distribution, 1955 - Planning Commission (Planning Commission Government of India, 1957)
The 1955 Report on Engineers in India, conducted by the Planning Commission’s Scientific and Technical Manpower Division with the Indian Statistical Institute, provides a comprehensive analysis of the nation’s engineering workforce at the onset of the Second Five-Year Plan. The study estimated approximately 72,000 engineers, including 31,200 graduates and 40,700 diploma holders, with low unemployment rates. Two-thirds of graduates were employed in the public sector, predominantly in civil, mechanical, and electrical engineering roles, with central and state government departments absorbing nearly 70% of engineers. The report highlights rapid growth in engineering education, substantial regional variations, and a young workforce profile. These findings offer critical insights for planning and projecting engineering manpower requirements to support India’s industrialization and infrastructure development.
Planning Commission Scientific and Technical Manpower Division
Planning Commission Scientific and Technical Manpower Division
Keywords: Engineers; India; 1955; Graduate Engineers; Diploma Holders; Public Sector Employment; Civil Engineering; Mechanical Engineering; Electrical Engineering; Engineering Education; Employment Trends; Planning Commission